2001
DOI: 10.1046/j.1365-2036.2001.00853.x
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholic acid alone or with chenodeoxycholic acid for dissolution of cholesterol gallstones: a randomized multicentre trial

Abstract: There is no substantial difference in the efficacy of combined ursodeoxycholic acid and chenodeoxycholic acid and that of ursodeoxycholic acid alone in terms of gallstone dissolution rate, complete gallstone dissolution, or relief of biliary pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…Diarrhoea was the single most frequent adverse event during UDCA treatment in patients with gallstone disease, and has been reported at an incidence of 2–9% 50 ,. 63–65 In patients with primary biliary cirrhosis, diarrhoea was rarely observed and was only incidentally reported in three of five large‐scale trials 12 ,. 14 , 16 An increased incidence of diarrhoea by UDCA might be expected in the treatment of patients with primary sclerosing cholangitis and inflammatory bowel disease.…”
mentioning
confidence: 99%
“…Diarrhoea was the single most frequent adverse event during UDCA treatment in patients with gallstone disease, and has been reported at an incidence of 2–9% 50 ,. 63–65 In patients with primary biliary cirrhosis, diarrhoea was rarely observed and was only incidentally reported in three of five large‐scale trials 12 ,. 14 , 16 An increased incidence of diarrhoea by UDCA might be expected in the treatment of patients with primary sclerosing cholangitis and inflammatory bowel disease.…”
mentioning
confidence: 99%
“…Combination of UDCA with chenodeoxycholic acid therapy enhances the biliary levels of UDCA [25]. Zuin et al [26] have obtained gallstone dissolution rate of 83% with UDCA plus chenodeoxycholic acid combination in 12 months, whereas Petroni et al [27] obtained a 30% dissolution rate with the same combination over 24 months. Moreover, Tazuma et al [28] have found 70% stone dissolution in multiple stones and 25% in solitary stones after 12 months treatment with UDCA.…”
Section: Discussionmentioning
confidence: 99%
“…(3) [71,72]. Finally, the efficacy of the bile acid UDCA in preventing gallstone related pain attacks and gallstone related complications (especially in patients with contraindications for operation or in those on the waiting list for laparoscopic cholecystectomy) should be investigated further , since two retrospective studies have demonstrated favourable outcomes for this strategy [73,74]. For this reason the results of a large double blind multi-center randomized controlled study of UDCA/Placebo treatment for symptomatic gallstone patients waiting for the laparoscopic operation on the waiting list in the Netherlands are anxiously awaited.…”
Section: Medication For Non-surgical Treatment Of Gallstone Diseasementioning
confidence: 98%